Exploring the Impact of Emerging Technologies on Corporate Communication: Challenges and Opportunities - Kalinichenko, Oleh; Ioanno, Vladyslav; Sydorenko, Tetyana; Mykhaylyova, Kateryna; Golub, Iuliia (Indian Journal of Information Sources and Services, 2025)
The article examines topical issues of introducing the latest technologies into corporate communication. The authors investigate the CommTech (communication technology) phenomenon within corporate landscape and present a methodology for researching its origins and ramifications. Innovations have become critically important in the dynamic development of the business environment and growing demands on employee productivity. Meanwhile, despite the growing number of studies devoted to the benefits of emerging technologies for corporate communication, they are mainly focused to certain restricted features and do not evaluate the existing and prospective obstacles. The article analyses the main communication tools used to interact with clients and between colleagues within the company. The research methodology is based on an empirical approach, which involves collecting and analysing secondary data from a Schneider survey conducted among 402 respondents. The data was processed using statistical methods. The study results showed that digital transformation in corporate communication has proliferated since 2019. Cloud services such as Microsoft Azure and Google Cloud Platform have helped reduce physical infrastructure costs by up to 40% and provide uninterrupted access to data 24/7 The companies successfully integrated project management tools, increasing employee productivity and optimising internal processes by 20%. The practical significance of the results lies in the possibility of using new technologies to increase productivity and organise an effective communication environment that will meet modern market challenges. Further research perspectives include studying the cultural and ethical aspects of technology implementation in international companies and analysing the impact of new communication models on the formation of corporate culture. The future of business communication is dependent on the smooth integration of these developing technologies. AI, VR, and interactive content are not distinct trends, but rather complimentary technologies that, when integrated, form a strong communication environment. The progress of technology will undoubtedly have an impact on the future of business communication. Interactive content and other innovations are more than simply trends; they are strategic tools that enable organizations to communicate more effectively, increase participation, and develop long-term connections with employees and stakeholders. Embracing these innovations will definitely propel businesses to the forefront of the corporate communication environment, enbling success in an era defined by innovation and connectedness.